STRATEGI BRAND EXPERIENCE UNTUK MEMENANGKAN PERSAINGAN DAN MENINGKATKAN LOYALITAS PELANGGAN PADA KEDAI KOPI ALADEEN COFFEE - Mohammad Haidar Ali; M. Adi Trisna Wahyudi; Kusnul Ciptanila Yuni K (JURNAL ILMIAH EDUNOMIKA, 2024)
Marketing is an activity that is very important and must be carried out by entrepreneurs in running their business in order to sustain their business, so that they can ignore competition and increase customer loyalty. Aladeen Coffee is one of the coffee shops in Jombang that wants to win the competition and increase customer loyalty in its new location by implementing a Brand Experience strategy that provides experience is more than just enjoying a coffee or other menu to the customer. This study used a qualitative descriptive method, using primary data sources obtained from four informants, namely the owner and three loyal customers of Aladeen Coffee through passive participatory observation, structured interviews, and documentation. The data analysis technique in this study uses data reduction, data presentation, and drawing conclusions. The results of this study are expected to contribute ideas to business people and further research.